SEMIOTIC ANALYSIS ON THE SERIES OF “TEMU MANTEN” IN MALANG - Herastanti Putri Agustin; Ika Nurhayani; Sigit Prawoto (UIBU, 2022)
Indonesia has lots of culture, especially in Java. Javanese people still uphold their culture, it can be seen from the many ceremonies and rituals they do. There is one ceremony that is still held up until now, and that is Temu Manten. Temu Manten is a highlight of the Javanese traditional wedding, which has meaning as the meeting of the bride and the groom. There are lots of symbols there that represent the marriage life. The study related to symbols is semiotic. Based on Barthes’s theory, semiotic consists of denotative, connotative, and myths. This study aims to analyze the semiotic meaning on the series of Temu Manten that occurs in Malang. This study used qualitative method and used Barthes’s theory to analyze the data. The source of the data is from the interviewing the informant and some books that related to Temu Manten. The data collected in May 11th, 2022 in Kepuharjo, Malang, East Java. The data collected by using these techniques, such as: 1) Observing and taking notes; 2) Interviewing the informant.; 3) Recording and taking note.; 4) Transcribing. The data was analyzed by using Roland Barthes’s theory about denotative, connotative and myth. The result showed that the groom and the bride must be nice family and helpful to others. Where the family will always support and guide them to face a harmonious home life. In facing domestic life, keep learning to process the feelings and intentions that have been given by God to be able to understand one another.